Pengaruh Penerapan Otonomi Desa Terhadap Partisipasi Masyarakat Dalam Pembangunan (Suatu Studi Di Distrik Saifi Kabupaten Sorong Selatan) - Ajamsaru, Yonadap; Rorong, Arie Junus; Londa, Very (JURNAL ADMINISTRASI PUBLIK, 2016)
Abstract: This research moved from the initial observation that the application by the amah VillageAutonomy Law. No. 6 Year 2015 About the Village is not optimal so that the impact on the low participation ofrural communities, especially in the district of South Sorong Regency Saifi. Thus, this study aimed to analyzethe effect of implementation of village autonomy to public participation in the development of Saifi village inthe district of South Sorong regency. Denagn applying the method of descriptive and quantitative approachesand applying imntrumen questionnaire, distributed to 46 people selamnjutnya government officials Kampungdistributed into five villages. After the data and information collected, then processed and analyzed by usingfrequency tables and analysis product moment correlation analysis and simple linear regression to test thehypothesis.The results of data analysis menunkkan that (1). The implementation of village autonomy is in thecategory "medium" tend to be "low", while the level of community participation in rural development are inthe category of "moderate" tend to be "high". (2). The implementation of village autonomy as one of the factorsthat influence people's participation in rural development. The implementation of village autonomy contributepositively and significantly on the level of participation of rural communities, especially in the district of SouthSorong Regency Saifi. Thus, it can be concluded that the hypothesis can be tested by empirical validity as wellas to justify the underlying theories.It is necessary to give some suggestions, among others: (1). Not optimal application of Village Autonomy,it is expected that the government (district / city and province) is committed to delegate authority under thelegislation in force regarding some matters that are directly handled by the village government so as toencourage an increase in the intensity of the implementation of village autonomy. (2). It is recommended thatthe local government encourages well as streamline the functions of village institutions as a partner with thevillage government through education and functional training.Keywords: Autonomy village, community participation, rural development